Estimating particle size of hydrocyclone underflow discharge using image analysis - Uahengo, Foibe Dimbulukwa Lawanifwa (Stellenbosch : Stellenbosch University, 2014)
Thesis (MScEng)--Stellenbosch University, 2014.